Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Lembaga Perlindungan Konsumen Republik Indonesia Cabang Kediri - Mochammad Sulistiyanda; Iing Sri Hardiningrum; Anita Sumelvia Dewi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
Employee performance is the main factor to help the company achieve its goals. One of the efforts to improve employee performance is the provision of compensation and work discipline. The indicators of this compensation are incentives and salary. While the indicators of work discipline are punctuality, high responsibility, obedience to office rules. By knowing this relationship, the LPK-RI Kediri can estimate how the employee's response regarding the compensation and work discipline provided, so as to have maximum employee performance results.This research is a descriptive quantitative research that aims to produce a discovery obtained through statistical procedures. The sample in this study used a saturated sample with 50 employees as respondents. The data in this study were obtained through observation, interviews, questionnaires and literature study. From the results of the analysis that has been done. The results of the study show that compensation and work discipline have an effect on employee performance. This is evidenced by the results of the R Square value of 0.694 or 69.4% while the remaining 30.6% is influenced by other variables.